2006
DOI: 10.2527/2006.8461544x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing flax in beef feedlot diets on performance, carcass characteristics, and trained sensory panel ratings1

Abstract: To assess the effects of flax addition and flax processing on feedlot performance and carcass characteristics, 128 yearling beef heifers (360 +/- 14 kg of initial BW) were blocked by weight and assigned randomly to feedlot diets that included no flax (control), whole flax (WHL), rolled flax (RLD; 1,300 microm), or ground flax (GRD; 700 microm). Heifers were fed a growth diet (31% corn, 30% corn silage, 18% barley malt pellets, 14% alfalfa, 4% linseed meal, and 3% supplement; DM basis) for 56 d, after which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 27 publications
8
50
6
Order By: Relevance
“…It can also be noted that pasture feeding, which is another source of 18:3 n-3, increases 18:3 n-3 in meat, although generally to a lower extent (Scollan et al, 2005). The increase in muscle 18:3 n-3 concentration is significantly higher with extruded linseeds than with rolled linseeds (Normand et al, 2005), and higher in ground or rolled linseeds than with whole linseeds (Maddock et al, 2006). The increase in 18:3 n-3 was higher in Longissimus thoracis than in Rectus abdominis and Semitendinosus in a trial by Mialon et al (2015), but this difference was not observed in trials by Normand et al (2005) and by Habeanu et al (2014).…”
Section: Linseed a Provider Of Omega-3 For Ruminantsmentioning
confidence: 75%
See 3 more Smart Citations
“…It can also be noted that pasture feeding, which is another source of 18:3 n-3, increases 18:3 n-3 in meat, although generally to a lower extent (Scollan et al, 2005). The increase in muscle 18:3 n-3 concentration is significantly higher with extruded linseeds than with rolled linseeds (Normand et al, 2005), and higher in ground or rolled linseeds than with whole linseeds (Maddock et al, 2006). The increase in 18:3 n-3 was higher in Longissimus thoracis than in Rectus abdominis and Semitendinosus in a trial by Mialon et al (2015), but this difference was not observed in trials by Normand et al (2005) and by Habeanu et al (2014).…”
Section: Linseed a Provider Of Omega-3 For Ruminantsmentioning
confidence: 75%
“…It can be concluded that the incorporation of linseeds for finishing cattle has no effect or a slightly positive effect on performances. Although it has been shown that lipid supply in fattening diets generally increases carcass fat proportion (Clinquart et al, 1995), available data for linseed supply do not fully support this statement: linseeds may increase or not (Maddock et al, 2006;Normand et al, 2005;Razminowicz et al, 2008) carcass fatness. The reality of a difference between linseed and other lipid sources needs further research.…”
Section: Increasing the Use Of Linseed: Potential And Limitsmentioning
confidence: 81%
See 2 more Smart Citations
“…Although the scores for this attribute were over half of the scale in all treatments, tenderness was the greatest in meat from linseed fed animals (6.59), although the addition of CLA together with linseed decreased this perception (5.88) ( Table 4). Also Maddock et al (2006) found that meat from flaxseed fed animals was more tender than meat from steers finished on a corn-based diet without flaxseed. Since fibrousness is negatively related to tenderness (Campo et al, 1999), Mean scores rated from 0 = very low to 10 = very high.…”
Section: Resultsmentioning
confidence: 96%